PERBANDINGAN KEJADIAN PENINGKATAN TEKANAN DARAH PADA TRIMESTER II BERDASARKAN LAJU FILTRASI GLOMERULUS (LFG) - Joserizal Serudji; Rizanda Machmud (Universitas Andalas, 2019)
During normal pregnancy, glomerolus filtration rate (GFR) is increased so that the concentration of urea and creatinine decreased. With the onset of hypertension in pregnancy, renal perfusion and glomerular filtration decreases, the greater of decline showed more severe illness. This was an observational analytic study with Cohort design and performed in Obgyn Department of M. Djamil Hospital Padang, general district hospital in Batusangkar and Achmad Mukhtar, Private Practice Midwife in Batusangkar from June-December 2014. 100 samples of first trimester of pregnancy, each subject were examined ureum, creatinine, cystatin-c and glomerular filtration rate (GFR) based on CKD-EPI Cystatin and Creatinine 2012 Equation formula. Then divided into two groups, high glomerular filtration rate (GFR) high and low glomerular filtration rate (GFR) group. Each subject was evaluated blood pressure every 3 weeks and statistical analysis was done using the Independent samples test and chi square. There was significant association difference in the levels of urea, creatinine and cystatin-c between high GFR group and low GFR group (p <0.05). There was a statistically significant relationship between low GFR group of pregnant women with changes in systolic and diastolic blood pressure that persists or increases of 5-10 mmHg (p <0.05).Keywords: Preeclampsia, glomerular filtration rate (GFR), ureum, creatinine, cystatin-c, blood pressure